Purification and Characterisation of Malate Dehydrogenase From Synechocystis sp. PCC 6803: Biochemical Barrier of the Oxidative Tricarboxylic Acid Cycle - Takeya, Masahiro; Ito, Shoki; Sukigara, Haruna; Osanai, Takashi (Frontiers in Plant Science, 2018)
Cyanobacteria possess an atypical tricarboxylic acid (TCA) cycle with various bypasses. Previous studies have suggested that a cyclic flow through the TCA cycle is not essential for cyanobacteria under normal growth conditions. The cyanobacterial TCA cycle is, thus, different from that in other bacteria, and the biochemical properties of enzymes in this TCA cycle are less understood. In this study, we reveal the biochemical characteristics of malate dehydrogenase (MDH) from Synechocystis sp. PCC 6803 (SyMDH). The optimal temperature of SyMDH activity was 45–50°C and SyMDH was more thermostable than MDHs from other mesophilic microorganisms. The optimal pH of SyMDH varied with the direction of the reaction: pH 8.0 for the oxidative reaction and pH 6.5 for the reductive reaction. The reductive reaction catalysed by SyMDH was activated by magnesium ions and fumarate, indicating that SyMDH is regulated by a positive feedback mechanism. The Km value of SyMDH for malate was approximately 210-fold higher than that for oxaloacetate and the Km value for NAD+ was approximately 19-fold higher than that for NADH. The catalytic efficiency of SyMDH for the reductive reaction, deduced from kcat values, was also higher than that for the oxidative reaction. These results indicate that SyMDH is more efficient in the reductive reaction in the TCA cycle, and it plays key roles in determining the direction of the TCA cycle in this cyanobacterium.